MUTU TEH HERBAL DAUN KEJI BELING DENGAN PERLAKUAN LAMA PENGERINGAN - ARJELINA FITRIANA; NOVIAR HARUN; YUSMARINI YUSMARINI (Universitas Riau, 2017)
The purpose of this study was to the best drying time on the quality of herbal tea of keji beling leaves. Thisstudy used a Completely Randomized Design with four treatments and four replications. The treatment usedherbal tea of keji beling leaves were P1 (120 minutes dying), P2 (150 minutes drying), P3 (180 minutesdrying), and P4 (210 minutes drying). The data obtained statistically using ANOVA and DNMRT at 5% level.Results of the study showed that the drying time significantly affected the moisture and ash contents, antioxidantactivity, polyphenol content, and the sensory assessment descriptive and hedonic tests. The best treatment ofthe result was P2 treatment (150 minutes drying) which had moisture content 7.36%, ash 3.19%, antioxidantactivity 10.79 μg/ml, polyphenols 15.63%, a little green color, slightly keji beling leaves flavor and a littletart taste. An overall assessment of herbal tea from keji beling leaves was rather to be liked by the panelists.